Phosphorylation and dephosphorylation regulate the Fanconi anaemia DNA repair pathway - Yang, D (2023)

(untitled)
Interstrand crosslink (ICL) is a highly deleterious form of DNA damage as crosslinked DNA double strands block DNA replication, transcription machinery and prevent chromosome segregation. One of the major pathways for resolving DNA ICL damage is the Fanconi anaemia (FA) pathway, of which recruitment of the FANCD2/FANCI complex to sites of ICL damage is crucial for its repair by the FA pathway. The activity of FANCD2/FANCI complex is tightly regulated by post-translational modifications. Monoubiquitination of the FANCD2/FANCI complex lead to their retention on chromatin, which is essential for subsequent repair events to occur. However, it is believed that ubiquitination takes place after the recruitment of the FANCD2/FANCI complex to DNA, thus how recruitment of the complex is regulated still remains to be investigated. Our group reported a previously unknown kinase CK2 dependent phosphorylation event on FANCD2 at a six-residue cluster spanning from residue 882-898, which reduces the activity of FANCD2/FANCI complex, hence blocking subsequent events in the FA pathway. Phosphorylation of FANCD2 by CK2 restrains not only recruitment of FANCD2/FANCI complex to DNA but also FANCD2 monoubiquitination, pointing to an inhibitory effect on the function of the complex to prevent cells from spurious activation of repair in unperturbed conditions. We speculated that an unknown phosphatase may antagonize the effect of CK2 and promote the repairing function of FANCD2/FANCI complex during ICL repair. Here we identified one of the members belonging to the protein serine/threonine phosphatase PP2A family, PPP2R3A/PP2A, as the major phosphatase that specifically dephosphorylates and therefore activates CK2-phosphorylated FANCD2 during ICL repair. Silencing the catalytic activity of PPP2R3A/PP2A led to reduced recruitment and ubiquitination of FANCD2 upon induction of ICL damage. Importantly, cells lacking active PPP2R3A/PP2A displayed a deficient activation of the FA pathway, including increased sensitivity to ICL inducing reagent MMC. Our results describe a novel regulatory mechanism in which the function of FANCD2/FANCI complex is tightly regulated by the dynamic phosphorylation and dephosphorylation events mediated by CK2 and PP2A. In addition, PPP2R3A/PP2A that activates FANCD2 could serve as a potential druggable target to overcome chemotherapy resistance to ICL inducing reagents such as cisplatin, as the major mechanism of developing drug resistance is via an over-activated FA pathway.